Choriocarcinoma of uterine cervix with cerebral and lung metastasis - Ansari, MA; Pokhrel, LR; Thapa, R; Shrestha, DM; Pradhan, S (Journal of Institute of Medicine Nepal, 2009)
<!--[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]--><!--[if gte mso 9]> <![endif]--> <!--[if gte mso 10]> <![endif]--> The full text of this paper is available from the Journal of Institute of Medicine website Journal of Institute of Medicine, April, 2009; 31:1 26-29